Mining industry as one of the priority sectors of economy of the Republic of Armenia - Петросян, С. А. (Scientific Progress & Innovations, 2012)
The importance and necessity of the mining industry in the further development of Armenian economy are well-grounded in this article. Moreover its negative impacts on the environment are elicited and measures for their reduction are proposed. According to the Director of the Research Center for EcoNoosphere studies NANRA A. Saghatelyan, environmental pollution by heavy metals takes place to such an extent that it leads to the penetration of heavy metals in the food production circle. This fact is observed almost in all mining regions of Armenia: in the South, in the North, in the Ararat Valley as well. Through sewage the metals have contaminated not only the ground itself, but irrigation water too. All of this injurious stuff goes into vegetable products, presenting a great danger to human health. This is a real threat for disruption of the gene pool.